Fish consumption and track to a fish feed formulation - Soong, Cai Juan; Razamin, Ramli; Rosshairy, Abdul Rahman (AIP Publishing LLC, 2015)
Strategically located in the equator, Malaysia is blessed with plenty of fish supply. The high demand in fish consumption has helped the development in the fishery industry and provided numerous jobs in the secondary sector, contributing significantly to the nation’s income. A survey was conducted to understand the trend of current demands for fish for the purpose of designing a feed formulation, which is still limited in this area of study. Results showed that grouper fish in restaurants commanded a very high price compared to other species of fish. Tiger grouper gained the highest demand in most restaurants, while giant grouper had the highest price in restaurants. Due to the demand and challenges to culture this type of fish, a framework for fish feed formulation is proposed. The formulation framework when materialized could be an alternative to the use of trash fish as the feed for grouper.